Investigating the Use of Peer Feedback as a Strategy in Teaching Descriptive Text - Oktaviani, Helda; Azis, Abdul; Juniardi, Yudi (Journal of English Language Teaching and Cultural Studies, 2024)
This study aims to investigate the use of peer feedback strategy in teaching descriptive text writing in XI-5 students at SMAN 10 Pandeglang by using a qualitative case study approach. Data collection methods include classroom observation and semi-structured interviews with students and teacher. Classroom observation was conducted to observe the implementation process of peer feedback directly in the classroom while learning descriptive text writing. Furthermore, semi-structured interviews were conducted individually with several students and teachers involved in the study. The interviews with students aimed to explore their perceptions and challenges using peer feedback, and their impact on writing quality and learning motivation. Meanwhile, interviews with teachers focused on the approach used in implementing peer feedback, the obstacles faced, and their views on the strategy's effectiveness. The results showed that peer feedback helped students develop better descriptive text-writing skills, especially regarding word selection, idea organization, and description sharpness.